Balance environmental obligations and socio-economic compulsion; the case of Kadamaian’s indigenous community proficiency needs - Robert Francis Peters (Universiti Malaysia Sabah, 2021)
The community of Kadamaian is expected to have heightened sense of environmental and biodiversity awareness and an obligation towards protection and conservation since the community occupies an area adjacent to Sabah’s premier World Heritage Site i.e. Kinabalu Park. Of course, with support from the Sabah government, Kadamaian's community is compelled to exploit their natural surroundings as primary resources to better their socio-economic position to be at par with other communities elsewhere in Sabah. Will Kadamaian’s community be able to balance the obligation and the compulsion to exploit? An empirical study in a scientific expedition that was carried out in late 2019 at Kadamaian-Kota Belud answers this question. The unit of analysis in this study is the social relationship between Kadamaian’s community and its social artifacts. The documentation technique, direct observation technique and the interview technique were used to collect data, while data analysis was carried out according to the structuration theory using the triangulation method. The findings of this study showed the existence of three (3) interdependent social relationships that influenced Kadamaian’s community strive to balance environmental and socio-economic issues. While these relationships have somewhat contributed to the establishment of a non-governmental organization i.e. Kadamaian Biocultural Protocol Committee that focused on the environmental obligation of Kadamaian’s community, other small enterprising network focused on socio-economic compulsion. The implication of these relationships is discussed in the article.